Menstrual Disorders from Puberty to Early Adult Age: A Cross-Sectional Survey - Krupa Hitesh Shah; Anjum Afsha; Jyoti Bali; Shashikala Bhat (Journal of Clinical and Diagnostic Research, 2017)
Introduction: A female encounters various menstrual disorders from puberty to menopause. We evaluated menstrual disturbances in post-menarche age and young adult age. Aim: To know the prevalence and impact of menstrual abnormalities at early adolescent and young adult age and to evaluate course of disorders identified at early adolescent age. Materials and Methods: A cross-sectional survey was carried out through self-administered questionnaire on 367 consented students at Melaka Manipal Medical College at Manipal, during December 2015- April 2016. Data were analysed by Statistical Package for the Social Sciences (SPSS) 16.0 software. Results: Prevalence and pattern of menstrual disorders at early adolescent and at young adult age were noted. The mean age of menarche was 12.1 ±1.1 years. Menorrhagia was the most frequent (14.7% and 11.7%) and polymenorrhea (7.6 % and 6%) was least frequent menstrual disorder at adolescent age and young adult age respectively. Resolution of pubertal menstrual disorders was observed in all disorders, but noticed highest in oligomenorrhea (91%), (p-value <0.05). Prevalence of menstrual related disorder like dysmenorrhea was 88.7% at adolescent age and 67.6% at the young adult age. It was statistically significant reduction. Hindrance in academic performance and social behavior was noted more at young adult age, which was in 23.9% and 46.7% respectively (p-value <0.05). Conclusion: The most prevalent menstrual abnormality was menorrhagia at the early adolescent and the young adult age. Associated the most prevalent menstrual related symptoms were dysmenorrhea at early adolescent age, and premenstrual symptom at the young adult age. The study demonstrates the natural course (decreasing prevalence) of all menstrual disorders from early adolescent to young adult age.